Incidence of Monomicrobial Staphylococcus aureus Bacteremia: A Population-Based Study in Olmsted County, Minnesota—2006 to 2020. (13th April 2022) - Hindy, Joya Rita; Quintero-Martinez, Juan A; Lahr, Brian D; Palraj, Raj; Go, John R; Fida, Madiha; Abu Saleh, Omar M; Arshad, Verda; Talha, Khawaja M; DeSimone, Daniel C; Sohail, M Rizwan; Baddour, Larry M
Abstract: Background: Population-based studies of Staphylococcus aureus bacteremia (SAB) in the United States are limited. We provide a contemporary evaluation of SAB incidence in Olmsted County, Minnesota, from 2006 to 2020. Methods: This was a retrospective population-based study of all adult patients with SAB residing in Olmsted County from 1 January 2006 through 31 December 2020. Initial episodes of SAB were identified using the microbiology laboratory databases at both Olmsted Medical Center and Mayo Clinic Rochester. Results: Overall, 541 incident SAB cases were identified with a median age of 66.8 (interquartile range, 54.4–78.5) years, and 60.4% were male. Among these cases, 298 (56.2%) were due to methicillin-susceptible S aureus (MSSA) and 232 (43.8%) cases of methicillin-resistant S aureus (MRSA). The overall age- and sex-adjusted SAB incidence rate (IR) was 33.9 (95% confidence interval [CI], 31.0–36.8) cases/100 000 person-years (PY). Males had a higher age-adjusted IR of 46.0 (95% CI, 41.0–51.0) cases/100 000 PY compared to females (IR, 24.4 [95% CI, 21.1–27.7] cases/100 000 PY). Age- and sex-adjusted SAB IRs due to MSSA and MRSA were 18.7 and 14.6 cases/100 000 PY, respectively, and the percentage of incident SAB cases due to MRSA fluctuated across the study period. There was no apparent temporal trend in SAB incidence over the study period ( P = .093). Conclusions: Our investigation represents the only contemporary population-based study in the United States. Despite the impression that SAB incidence may have increased based on Centers for Disease Control and Prevention surveillance data, our finding of no change in SAB incidence was somewhat unanticipated.